PENGARUH KEPEMILIKAN MANAJERIAL, PROPORSI KOMISARIS INDEPENDEN TERHADAP KUALITAS LABA - Riswandi, Pedi (Ekombis Review, 2014)
Pedi Riswandi; Ownership structure is very important because it is closely related to the operational control of the company . From the point of view of the theory of accounting , earnings management is determined by the motivation of the company manager . Different motivations will result in a different amount of earnings management , such as the manager who also shareholders of the company with a manager who is not a shareholder and board composition also plays an important role in control of what is done by the executive This study aimed to determine the effect of managerial ownership on earnings quality and the proportion of independent directors on the quality of earnings. The research sample using companies listed in Indonesia Stock Exchange in 2009-2011. "The technique of purposive sampling method. " These results indicate that managerial ownership has a negative effect on the quality of earnings , proportion of independent directors has a positive effect on the quality of earnings.Â Key words:Managerial ownership, Proportion Independent Commissioner , Earnings Quality